Introducing ELTE TÓK’s Kindergarten Education BA Programme - Nemes, Zsófia (Gyermeknevelés Tudományos Folyóirat, 2023)
The paper gives a short overview of the Kindergarten Education BA Programme offered by ELTE TÓK.